Imaginarios y estrategias decoloniales - Ferrera-Balanquet, Raúl Moarquech (Estudios Artísticos, 2018)
Enunciando el delinking de la matriz moderna/ colonial, este artículo imagina un territorio crítico teórico creativo partiendo de la aesthesis decolonial con el fin de dialogar con una serie de hacedores culturales que emplean estrategias creativas decoloniales en proyectos creativos. Un acercamiento a la exposición Haceres Decoloniales (2015) realizada en Bogotá, ofrece la oportunidad de conversar sobre el hacer creativo de Benvenuto Chavajay, Rosa Tisoy Tandoy y Marco Alonso Roa. Los efectos de la colonialidad sonora conllevan a dialogar con la artista maya k´iche Sandra Monterroso y el creador maya yucateco Isaac Carrillo Can. Discursamos sobre el proyecto Espejo Negro (2010) de Pedro Lasch y el mural Las Aguas Sagradas de La Llorona (2004) de la artista xicana Juana Alicia. Terminamos con una interpretación crítica sobre el proyecto Mariposa Memoria Ancestral (2013-2015), y el performance multidisciplinario Whip It Good (2013) de la artista danesa trinitobaguense Jeannette Ehlers. En reliant la déconnexion de la matrice moderne / coloniale, cet article imagine un territoire créatif- théorique-critique à partir de l’aesthésis décoloniale, afin de dialoguer avec une série d’acteurs culturels qui utilisent des stratégies décoloniales créatives dans des projets créatifs. Une approche de l’exposition Haceres Decoloniales (2015) tenue à Bogotá, offre l’occasion de parler du travail créatif de Benvenuto Chavajay, Rosa Tisoy Tandoy et Marco Alonso Roa. Les effets de la colonialité sonore impliquent un dialogue avec l’artiste maya k’iche Sandra Monterroso et le créateur maya yucatècque Isaac Carrillo Can. Nous parlons du projet Espejo Negro (2010) de Pedro Lasch et de la peinture murale Las Aguas Sagradas de La Llorona (2004) de l’artiste chicane Juana Alicia. Nous terminons avec une interprétation critique du projet Mariposa Memoria Ancestral (2013-2015) et la performance pluridisciplinaire Whip It Good (2013) de l’artiste danois né en Trinité-et-Tobago Jeannette Ehlers.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Only Skin Deep: Changing Visions of the American Self - Fusco, Coco; Wallis, Brian (Abrams and International Center of Photography, 2003)
"By bringing together a provocative selection of essays and images, Only Skin Deep: Changing Visions of the American Self addresses the issues of nation, race, and selfhood and how they are depicted in ways that are challenging and informative, prompting readers to consider the impact of photography on our everyday lives." "If photographs are chiefly responsible for perpetuating myths of American identity, can a different reading of these representations break down distorting stereotypes? This is the central question posed by Only Skin Deep. The authors in this book forcefully argue that race and nation - and, indeed, photography itself - are fictions, cultural constructions that shape our social interactions. Even as symbols, these photographic depictions of ethnic difference and cultural superiority have very real consequences. This collection of works and essays addresses, for example, the lingering consequences of American colonial expansion; the conflict between public and private visualizations of individuals; the role of commercial imagery in shaping gender roles; the impact of fantasy in ethnic or ethnographic photography; and the uses of science to provide justification for politicized depictions of "race."" "Accompanying a major exhibition of the same name, Only Skin Deep offers a critical rereading of the archive of the history of photography. This applies to the works of famous photographers - such as Dorothea Lange, Walker Evans, Ansel Adams, and Edward Steichen - as well as lesser-known historical figures, including Charles Eisenmann, Frances Benjamin Johnston, Will Soule, and Toyo Miyatake. A substantial part of the book is devoted to contemporary artists and photographers who have moved beyond the multicultural approach to representations of "race" and have made an investigation of the semiotics of cultural identity a prevalent theme over the past decade. Among the recent photographers included are: Nancy Burson, Nikki S. Lee, Glenn Ligon, Paul Pfeiffer, Hulleah Tsinhnahjinnie, Cindy Sherman, Lorna Simpson, and Andres Serrano."--(BOOK JACKET)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

African American Art and Artists - Lewis, Samella (University of California Press, 2003)
Samella Lewis has brought African American Art and Artists fully up to date in this revised and expanded edition. The book now looks at the works and lives of artists from the eighteenth century to the present, including new work in traditional media as well as in installation art, mixed media, and digital/computer art. Generously and handsomely illustrated, the book continues to reveal the rich legacy of work by African American artists.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Black Art: Ancestral Legacy : The African Impulse in African-American Art. - Dallas Museum of Art (Dallas Museum of Art, 1990)
For the first time, a major exhibition examines the impact of African culture on black artists, both trained and self-taught, in a stunning range of 157 works which are variously bold, witty, historical, and mysterious. 49 biographical outlines; 320 illustrations, 170 in full color.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Making Race : Modernism and Racial Art in America - Francis, Jacqueline (University of Washintong Press, 2012)
A history of a past phenomenon - racial art - which has ramifications for the present.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé